COVID-19 Lockdown and Implications for Household Food Security in Zambia: Quality of Diet or Economic Vulnerability? - Richard Bwalya; Chitalu Miriam Chama-Chiliba (Economies, 2025)
The study examines changes in household food security and identifies their key determinants in Zambia by comparing the pre-pandemic period to the COVID-19 pandemic period. Using nationally representative surveys from 2015 and 2021 and the coarsened exact matching (CEM) approach, 8650 households were matched for comparison. Two complementary food security measures are analysed using multinomial logit regression models: household expenditure share, representing economic vulnerability, and household dietary diversity score (HDDS), representing diet quality. The results show that household food expenditure share significantly increased from 53.8% to 61.4%, indicating increased economic vulnerability. Notably, household dietary diversity improved from 7.1 to 8.2 out of 12, indicating better dietary quality. Consistent determinants of food security—such as household size, education level, marital status, region, and employment—remained significant, but their protective effects weakened during the pandemic. Specifically, the protective effect of education declined, urban households became relatively more vulnerable, and wealthier households experienced minimal changes. The study recommends targeted interventions, including expanding social protection programmes for economically vulnerable households, supporting informal food markets, enhancing rural–urban food supply linkages, and promoting nutrition education to ensure diverse, affordable food access during crises.